Controlling the L‐Asparaginase extraction and purification by the appropriate selection of polymer/salt‐based aqueous biphasic systems - Magri, Agnes (2020)
BACKGROUND: L-Asparaginase (ASNase) is an important biopharmaceutical for the treatment of acute lymphoblastic leukemia (ALL); however, with some restrictions due to its high manufacturing costs. Aqueous biphasic systems (ABS) have been suggested as more economical platforms for the separation/purification of proteins, but a full understanding of the mechanisms behind the ASNase partition is still a major challenge. Polymer/salt-based ABS with different driving-forces (salting-out and hydrophilicity/hydrophobicity effects) were herein applied to control the partition of commercial ASNase. RESULTS: The main results showed the ASNase partition to the salt- or polymer-rich phase depending on the ABS studied, with extraction efficiencies higher than 95%. For systems composed of inorganic salts, the ASNase partition was controlled by the polyethylene glycol (PEG) molecular weight used. Cholinium-salts-based ABS were able to promote a preferential ASNase partition to the polymer-rich phase using PEG-600 and to the salt-rich phase using a more hydrophobic polypropylene glycol (PPG)-400 polymer. It was possible to select the ABS composed of PEG-2000 + potassium phosphate buffer as the most efficient to separate the ASNase from the main contaminant proteins (purification factor = 2.4 ± 0.2), while it was able to maintain the enzyme activity for posterior application as part of a therapeutic. CONCLUSION: Polymer/salt ABS can be used to control the partition of ASNase and adjust its purification yields, demonstrating the ABS potential as more economic platform for the selective recovery of therapeutic enzymes from complex broths.